Energy efficiency of heating machines and its effects on broiler's performance and welfare (Scientia Agropecuaria, 2025)
The increasing global demand for animal protein has driven the broiler industry to optimize production systems and better understand limiting factors affecting performance. This study evaluated four different heating systems to determine their correlation with climatic variables, zootechnical performance, pellet fuel consumption, and energy usage. Data were obtained from a private broiler integration company in Southwest Paraná, Brazil, specializing in the griller broiler category. The study covered a 28-day housing period for 12 flocks (both male and female), each consisting of approximately 120,000 birds, for 28 days. The analyzed variables included indoor and outdoor environmental temperature, relative air humidity, carbon dioxide (CO₂) concentration inside the poultry houses, feed conversion ratio, weight gain, pellet fuel consumption, and energy consumption. Statistical analyses were performed using descriptive statistics and Principal Component Analysis (PCA) in R software. Results indicated that correlations among variables were generally weak. However, environmental conditions had the greatest influence on broiler performance. The first principal component explained 74.1% of the total variance, with minimum CO₂ concentration, external temperature, minimum and maximum internal temperature, and pellet fuel consumption being key contributing factors. The second principal component included maximum CO₂ concentration, weight gain, and minimum internal and external relative humidity. Among the evaluated heating systems, the fourth machine tested exhibited the lowest pellet fuel consumption while maintaining satisfactory weight gain and feed conversion rate despite its relatively high energy consumption. These findings suggest that temperature control and pellet fuel consumption are critical factors in optimizing broiler production efficiency, ultimately contributing to improved growth performance and resource utilization.
Keywords: poultry production; thermal comfort; heat system; productivity; gases concentration